Investigating Representation Ethos Émotif in 2007 French Presidential Election - Aprillia Firmonasari; Rosidin Ali Syabana (k@ta: A Biannual Publication on the Study of Languange and Literature, 2020)
The issue of immigration became prominent in French political discourse in 2005 that leads to debate about France and nationalism. During the lead-up to the 2007 French Presidential election, various concepts of a French national identity were promoted by candidates: Nicolas Sarkozy, Ségolene Royal, François Bayrou, and Jean-Marie Le Pen. Candidates gave particular attention to ethos, specifically ethos émotif. In this article, the researcher will characterize the ethos émotif presented by the four candidates mentioned above. The ethos will be then examined whether it were successfully embodied in these candidates' speeches by investigating the public reaction they received based on articles published in the French media. This research will apply a critical discourse analysis and interactional sociolinguistics approach using elements of interaction formulated by Stébe (2008) and Kerbrat-Orecchioni (1990). Data will be classified using the software LEXICO 3.